On- and off-line analysis by ICP-MS to measure the bioaccessible concentration of elements in PM10 using dynamic versions of the simplified bioaccessibility extraction test - Alpofead, Jawad Ali Hussein; Davidson, Christine M.; Littlejohn, David (Analytical and bioanalytical chemistry, 2023)
Two dynamic versions of the simplified bioaccessibility extraction test (SBET) were developed—an off-line procedure and an on-line procedure coupled directly to ICP-MS. Batch, on-line, and off-line procedures were applied to simulated PM 10 samples prepared by loading NIST SRM 2711A Montana II Soil and BGS RM 102 Ironstone Soil onto 45-mm TX40 filters widely used in air quality monitoring. Three real PM 10 samples were also extracted. A polycarbonate filter holder was used as an extraction unit for the dynamic procedures. Arsenic, Cd, Cr, Cu, Fe, Mn, Ni, Pb, and Zn were determined in the extracts using an Agilent 7700 × ICP-MS instrument. The residual simulated PM 10 samples following application of the SBET were subjected to microwave-assisted aqua regia digestion and a mass balance calculation performed with respect to digestion of a separate test portion of the SRM. Leachates were collected as subfractions for the off-line analysis or continuously introduced to the nebuliser of the ICP-MS for the on-line analysis. The mass balance was generally acceptable for all versions of the SBET. Recoveries obtained with the dynamic methods were closer to pseudototal values than those obtained in batch mode. Off-line analysis performed better than on-line analysis, except for Pb. Recoveries of bioaccessible Pb relative to the certified value in NIST SRM 2711A Montana II Soil (1110 ± 49 mg kg −1 ) were 99, 106, and 105% for the batch, off-line, and on-line methods, respectively. The study demonstrates that dynamic SBET can be used to measure bioaccessibility of potentially toxic elements in PM 10 samples.